The Mediating Role of Fear of the Future in the Association between Career Goal Inconsistency and Mental Health - Murat Aslan; Sevinç Namlı; Fatih Ateş (Journal of Education and Future, 2026)
Uncertainty and inconsistency in university students’ career goals may increase fear of the future and constitute an important risk factor for the emergence of psychological problems such as depression, anxiety, stress, and loneliness. This study aimed to examine the mediating role of fear of the future in the relationship between career goal inconsistency and depression, anxiety, stress, and loneliness among students studying at faculties of sport sciences. A correlational survey model was used in the study, and the data collected from 318 sport sciences students studying at universities in Türkiye were analyzed using structural equation modeling (SEM). In addition, the construct validity of the measurement instruments was evaluated through confirmatory factor analysis using χ², df, p, CFI, TLI, SRMR and RMSEA while their reliability was assessed using Cronbach’s alpha coefficient. The findings indicated that career goal inconsistency was significantly associated with fear of the future and that fear of the future might play a mediating role in explaining the relationships between career goal inconsistency and depression, anxiety, stress, and loneliness. The model explained 45.4% of the variance in fear of the future, 47.9% in depression, 45.3% in anxiety, 41.5% in stress, and 27.7% in loneliness. These results highlighted the importance of career counseling and psychological support practices for sport sciences students.